2007
DOI: 10.1007/s11244-007-0219-6
|View full text |Cite
|
Sign up to set email alerts
|

Heat and mass transfer limitations in pre-turbocharger catalysts

Abstract: The use of the Diesel engine is increasing, while at the same time emission limits are becoming more stringent. To reduce emissions, novel catalyst converter designs have been proposed, including the placement of a small converter before the turbocharger. The role of this catalyst is to provide some reduction of the pollutant level prior to the main catalyst. This catalyst is typified by high flow rates. In this paper the performance of small catalytic converters operated at high flowrate is examined using com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
2
8
0
1
Order By: Relevance
“…In fact, velocity suggested in [1] exceeds many times that commonly applied in chemical reactors and to our knowledge there is no information on the functioning the structured reactors in the literature.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…In fact, velocity suggested in [1] exceeds many times that commonly applied in chemical reactors and to our knowledge there is no information on the functioning the structured reactors in the literature.…”
mentioning
confidence: 92%
“…Therefore, novel methods of controlling CO/NO x emissions are still proposed to enhance the effectiveness of classic monolithic converters. For example, More et al [1] suggested preliminary pollution reduction in a small converter placed before the turbocharger. Assumed gas velocity may reach 100 m/s.…”
mentioning
confidence: 99%
See 3 more Smart Citations